Do I Love My Job? A Study of Job Satisfaction Among Generation Z Employees in the Coffee Shop Industry - Al’Fara Arum Suci Witjaksono; Febrianur Ibnu Fitroh Sukono Putra (International Forum of Researchers and Lecturers, 2025)
The growth of coffee shop businesses in Semarang has accelerated in line with the rising coffee consumption trend among younger generations. In this context, employees play a crucial role in ensuring service quality. However, job dissatisfaction triggered by work-related stress and excessive service load remains a significant challenge. This study aims to examine the influence of occupational strain, service load, reward fairness, supervisory support, and work-life balance on job satisfaction among coffee shop employees in Semarang. A quantitative approach was used through a survey method, utilizing a questionnaire distributed via Google Form. A total of 100 respondents from various coffee shops in Semarang were selected using a census technique. The results revealed that occupational strain and service load have a negative and significant effect on job satisfaction. Meanwhile, reward fairness, supervisory support, and work-life balance have a positive and significant impact on job satisfaction. These findings offer valuable insights for coffee shop owners in developing effective human resource strategies that promote employee wellbeing and maintain high service quality.